Substitutive proprioception feedback of a prosthetic wrist by electrotactile stimulation - Han, Yichen; Lu, Yinping; Zuo, Yufeng; Song, Hongliang; Chou, Chih-Hong; Wang, Xing; Li, Xiangxin; Li, Lei; Niu, Chuanxin M.; Hou, Wensheng (Frontiers in Neuroscience, 2023)
Objective. Sensory feedback of upper-limb prostheses is widely desired and studied. As important components of proprioception, position and movement feedback help users to control prostheses better. Among various feedback methods, electrotactile stimulation is a potential method for coding proprioceptive information of a prosthesis. This study was motivated by the need for proprioception information for a prosthetic wrist. The flexion-extension (FE) position and movement information of the prosthetic wrist are transmitted back to the human body through multichannel electrotactile stimulation. Approach. We developed an electrotactile scheme to encode the FE position and movement of the prosthetic wrist and designed an integrated experimental platform. A preliminary experiment on the sensory threshold and discomfort threshold was performed. Then, two proprioceptive feedback experiments were performed: a position sense experiment (Exp1) and a movement sense experiment (Exp2). Each experiment included a learning session and a test session. The success rate (SR) and discrimination reaction time (DRT) were analyzed to evaluate the recognition effect. The acceptance of the electrotactile scheme was evaluated by a questionnaire. Main results. Our results showed that the average position SRs of five able-bodied subjects, amputee 1, and amputee 2 were 83.78%, 97.78% and 84.44%, respectively. The average movement SR, and the direction and range SR of wrist movement in five able-bodied subjects were 76.25%, 96.67%, respectively. Amputee 1 and amputee 2 had movement SRs of 87.78% and 90.00% and direction and range SRs of 64.58% and 77.08%, respectively. The average DRT of five able-bodied subjects was less than 1.5 seconds and that of amputees was less than 3.5 seconds. Conclusion. The results indicate that after a short period of learning, the subjects can sense the position and movement of wrist FE. The proposed substitutive scheme has the potential for amputees to sense a prosthetic wrist, thus enhancing the human‒machine interaction.